6.9k views
5 votes
Please explain and show work

Please explain and show work-example-1

2 Answers

1 vote
Let's solve your equation step-by-step.(1 3/5)(t−6)= −0.4Step 1: Simplify both sides of the equation.8/5t + −48/5= −0.4Step 2: Add 48/5 to both sides.8/5t + −48/5 + 48/5 = −0.4 + 48/58/5t = 46/5Step 3: Multiply both sides by 5/8.(5/8)*(8/5t)=(5/8)*(46/5)t=23/4Answer:t = 5 3/4
User Nith
by
6.1k points
3 votes
1*3/5 = 3/5.
3/5(t-6) = -0.4
Distribute 3/5
3/5t - 3.6 = -0.4
Add 3.6
3/5t = 3.2
Divide by 3/5
t = 5 1/3 or 5.33
User Anthony Stringer
by
5.8k points